The portrayal of black women in Toni Morrison’s Beloved, The Bluest Eye, and Song of Solomon - Wajiran, Wajiran (Research Journal in Advanced Humanities, 2024)
This paper examines the complex themes of racial discrimination, gender injustice, and the intersection of race and gender in Toni Morrison’s Beloved, The Bluest Eye, and Song of Solomon. The main objective is to explain how Morrison’s narratives reveal the combined impact of these social issues on African-American individuals, particularly women. This study uses the theoretical framework of black feminism to understand the multiple layers of oppression that black women face in America. By conducting a comparative analysis of Morrison’s works, this study seeks to uncover the vision and mission underlying her literary exploration of these themes. Using black feminism as a guiding theory, it highlights the pervasive nature of racial discrimination and its adverse impact on identity and mental well-being, as depicted in characters such as Sethe and Pecola Breedlove. The analysis delves further into gender injustice, illustrating how Morrison’s female characters navigate and resist the patriarchal structures that exacerbate their marginalization. By comparing the characters’ experiences in Morrison’s novel, this study aims to comprehensively understand the interplay between race and gender in shaping black women’s lives and identities.